Blue Nevus of the Cervix, an Unusual Lesion – A Case Report - Şahin, Sevinç; Seçkin, Selda; Seçkin, Levent (International Journal of Pathology, 2018)
Blue nevus is a cutaneous melanocytic lesion characterized by the proliferation of dermal dendriticmelanocytes. In addition, blue nevus also has been rarely reported in various extracutaneous siteswhich are usually devoid of melanocytes such as oral mucosa, lymph nodes, maxillary sinus, pulmonaryhilus, orbit, conjunctiva, meninges, vagina, prostate, spermatic cord, and cervix. It is suggestedthat these lesions may originate from either Schwann cells of the stromal nerves or from melanocyticprecursors migrated from neural crest. Herein, we present a rare case of blue nevus both inthe uterine cervical stroma and in the cervical polyp. Only about 100 cases have been reported so far.